Filament winding - Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2008)
The filament winding program examines both the wet winding and dry winding processes. The primary types of filament winding methods are detailed including: hoop winding and helical winding. This program also features an in-depth look at the types and uses of filament winding mandrels
Title from title screen
DVD format
Keywords: Reinforced plastics; Composite materials; Fibrous composites; Composite construction